Smart Financial Village : Penguatan Literasi Keuangan Masyarakat Melalui Edukasi Dalam Mewujudkan Kemandirian Financial - Diah Rahmawati; Neni Nurhayati (Redtech Putra Benua, 2026)
Abstract The low level of financial literacy in the community and the increasing use of online loans are challenges that can impact the economic well-being of families, particularly in rural areas. This condition is also experienced by the community of Padarama Village, Ciawigebang District, Kuningan Regency, who still have limitations in financial management, simple financial record-keeping, and understanding the risks of online loans. This community service activity aims to improve financial literacy and foster wiser financial behavior through the Smart Financial Village program. The methods used include outreach, education and training, implementation of simple digital-based financial record-keeping, mentoring, evaluation, and community formation as an effort to sustain the program. The innovation implemented utilizes a simple spreadsheet, a financial habit tracker, and WhatsApp as a means of education and mentoring. The expected results are increased community understanding of financial management, the development of household budgets, increased savings habits, and a reduced risk of unwise use of online loans. This program is expected to become a model for community empowerment capable of achieving sustainable financial independence.